Barriers and enablers to the delivery and implementation of the tailored activity programme in Australia: Perspectives of occupational therapists and their managers. (17th November 2022) - Bennett, Sally; Travers, Catherine; Liddle, Jacki; O'Connor, Claire; Low, Lee‐Fay; Laver, Kate; Clemson, Lindy; O'Reilly, Maria; Beattie, Elizabeth; Smith, Sandra; Gitlin, Laura
Abstract: Background: Prior to implementing new programmes or practices, it is essential to understand the context, barriers and enablers to support successful use. The tailored activity programme (TAP) is an evidence‐based intervention provided by occupational therapists to support community‐dwelling people living with dementia and their carers. The programme was developed in the United States, and although it is not currently available for routine use in Australia, its implementation would address the needs of many Australians with dementia and their carers. Aim: The aim of the study is to understand the perspectives of occupational therapists and their managers regarding barriers and enablers to the delivery and implementation of the TAP in Queensland, Australia. Methods: A qualitative descriptive methodology was employed. Semistructured interviews were undertaken with occupational therapists ( n  = 18) who work with community‐dwelling people with dementia and their carers, and their managers ( n  = 10). Participants were recruited from a range of organisations across Queensland, and they were asked about potential barriers and enablers to implementing TAP. Interviews were recorded and transcribed verbatim. Data were mapped using framework analysis whilst remaining open to other themes. Findings: Themes were identified, and facilitating factors included the close alignment of TAP with occupational therapists' scope of practice; their acceptance of, and optimism about the programme and its perceived benefits including improved client outcomes; and an opportunity for occupational therapists to further develop their skills. Managerial support and carers' readiness and willingness to participate were also identified as important factors for success, whereas barriers were cost to clients and the capacity of the occupational therapy workforce to provide TAP. Conclusion: Occupational therapists and their managers expressed enthusiasm for TAP and awareness of its likely benefits, while also identifying barriers that will need to be addressed if implementation of the programme is to be successful in Australia.